2016
DOI: 10.3349/ymj.2016.57.6.1404
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides to High-Density Lipoprotein Cholesterol Ratio Can Predict Impaired Glucose Tolerance in Young Women with Polycystic Ovary Syndrome

Abstract: PurposeThe triglycerides to high-density lipoprotein cholesterol (TG/HDL-C) ratio could be related to insulin resistance (IR). We previously reported that Korean women with polycystic ovary syndrome (PCOS) had a high prevalence of impaired glucose tolerance (IGT). We aimed to determine the cutoff value of the TG/HDL-C ratio for predicting IR and to examine whether the TG/HDL-C ratio is useful for identifying individuals at risk of IGT in young Korean women with PCOS.Materials and MethodsWe recruited 450 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…In a previous study with a smaller sample size of Iranian women with PCOS, the best cut-off point of TG/HDL-C and TC/HDL-C levels were 3.19 )sensitivity of 63.6%, specificity of 84.4%) and 4.37 )sensitivity of 69.7%, specificity of 65.6%), respectively [ 7 ]. In another study on the young Korean women with PCOS, the cut-off value of the TG/HDL-C ratio to predict the IR (estimated by the HOMA-IR index) was reported as 2.5 (sensitivity of 61%, specificity of 82%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study with a smaller sample size of Iranian women with PCOS, the best cut-off point of TG/HDL-C and TC/HDL-C levels were 3.19 )sensitivity of 63.6%, specificity of 84.4%) and 4.37 )sensitivity of 69.7%, specificity of 65.6%), respectively [ 7 ]. In another study on the young Korean women with PCOS, the cut-off value of the TG/HDL-C ratio to predict the IR (estimated by the HOMA-IR index) was reported as 2.5 (sensitivity of 61%, specificity of 82%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have shown that the triglyceride glucose (TyG) index is associated with IR, as assessed by hyperinsulinemic euglycemic clamp testing and HOMA-IR. Thus, the TyG index has been proposed as a reliable and simple surrogate marker of IR [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…TGL:HDL ratio is simple, cost-effective and useful tool to assess insulin resistance and cardiovascular disease in PCOS (Song et al, 2016). The highlight of the present study is the elevation of CRR-1, CRR-2 and markers of insulin resistance HOMA-IR and HOMA -adiponectin in PCOS women with TGL:HDL ≥ 3 that revealed the valuable effect of adiponectin against dyslipidemic environment.…”
Section: Resultsmentioning
confidence: 63%